2015
DOI: 10.1039/c5cp00311c
|View full text |Cite
|
Sign up to set email alerts
|

A crossed molecular beam and ab initio study on the formation of 5- and 6-methyl-1,4-dihydronaphthalene (C11H12) via the reaction of meta-tolyl (C7H7) with 1,3-butadiene (C4H6)

Abstract: The crossed molecular beam reactions of the meta-tolyl radical with 1,3-butadiene and D6-1,3-butadiene were conducted at collision energies of 48.5 kJ mol(-1) and 51.7 kJ mol(-1). The reaction dynamics propose a complex-forming reaction mechanism via addition of the meta-tolyl radical with its radical center either to the C1 or C2 carbon atom of the 1,3-butadiene reactant forming two distinct intermediates, which are connected via migration of the meta-tolyl group. Considering addition to C1 proceeds by format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The formation of these intermediates via van der Waals complexes and through barriers located below the energy of the reactants (submerged barriers) imply that these reactions are de-facto barrierless and can occur at very low temperatures, such as 10 K, prevailing in cold molecular clouds. Previous studies of aromatic radicals (phenyl, tolyl) reacting with 1,3-butadiene have found the channel leading to addition of the radical carbon to the central carbon atom not to be competitive relative to the addition to the CH 2 moiety even at elevated collision energies (Kaiser et al 2012;Parker et al 2014a;Muzangwa et al 2015). The central addition channel pathways were, therefore, omitted from present consideration as a competing channel in low temperature interstellar environments.…”
Section: Electronic Structure Calculationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The formation of these intermediates via van der Waals complexes and through barriers located below the energy of the reactants (submerged barriers) imply that these reactions are de-facto barrierless and can occur at very low temperatures, such as 10 K, prevailing in cold molecular clouds. Previous studies of aromatic radicals (phenyl, tolyl) reacting with 1,3-butadiene have found the channel leading to addition of the radical carbon to the central carbon atom not to be competitive relative to the addition to the CH 2 moiety even at elevated collision energies (Kaiser et al 2012;Parker et al 2014a;Muzangwa et al 2015). The central addition channel pathways were, therefore, omitted from present consideration as a competing channel in low temperature interstellar environments.…”
Section: Electronic Structure Calculationsmentioning
confidence: 98%
“…This mechanism adds to the increasing catalog of reactions involving phenyl-type aromatic radicals with the radical located on the aromatic ring, such as phenyl (Kaiser et al 2012), paratolyl (Parker et al 2014a), and meta-tolyl (Muzangwa et al 2015) with 1,3-butadiene and vinylacetylene that lead to facile PAH formation at low temperatures, through the formation of a van der Waals complex. PANH formation at low temperatures has implications for the astrochemistry of biologically relevant molecules.…”
Section: Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational methodology: A number of minima and saddle points were located on the potential energy surface to obtain equilibrium structures and transition states. The doubleended anharmonic downward distortion following (D-ADDF) methodology was used for search of the transition states [32][33][34][35]. The types of all the stationary points found were confirmed by harmonic frequency calculations.…”
Section: Methodsmentioning
confidence: 99%
“…11,15,16 Similarly, 1,3-butadiene can react with the ethynyl radical (CCH) to form benzene (C 6 H 6 ), 23 with the phenyl radical (C 6 H 5 ) to form 1,4-dihydronaphthalene (C 10 H 10 ), 41 or with the tolyl radical (C 7 H 7 ) to form 5-and 6-methyl-1,4-dihydronaphthalene (C 11 H 12 ). 42 Recently, it was shown that the methylacetylene molecule cannot be synthesized via gas-phase reactions alone. 27,43 An extensive review of the chemical pathways leading to methylacetylene in the gas phase concluded that there are no efficient gas-phase synthetic pathways available to reproduce the observed abundances of this molecule in the cold ISM.…”
Section: Introductionmentioning
confidence: 99%